A Phase I Study to Evaluate the Relative Bioavailability, Pharmacodynamics, and Safety of a Single Subcutaneous Injection of Recaticimab at Three Different Sites in Healthy Chinese Subjects - Wang, Ying; Cheng, Yuanzhi; Guo, Yuhan; Fan, Yang; Zhou, Renpeng; Zhang, Qian; Xu, Ye; Feng, Sheng; Shen, Kai; Hu, Wei (European journal of drug metabolism and pharmacokinetics, 2025)
Recaticimab (SHR-1209) is a humanized monoclonal antibody that binds to the proprotein convertase subtilisin/kexin type 9 (PCSK9) with high affinity. This study was conducted to compare the relative bioavailability, pharmacokinetics (PK), pharmacodynamics (PD), and safety of recaticimab following subcutaneous injection at three different sites in healthy Chinese subjects. In this randomized, parallel, open-label, phase I study, 159 healthy Chinese subjects were randomized to receive a single dose of 450 mg recaticimab subcutaneously into the abdomen, upper-arm, or thigh and were followed up until 113 days postdose. Adverse events were monitored, and serum samples were collected for PK, PD, and immunogenicity evaluation during the study. The PK profiles of recaticimab were similar among different injection site groups. The geometric mean ratios of maximum serum concentration (C ), area under the serum concentration versus time curve (AUC) from time zero to the time of last quantifiable concentration (AUC ), and AUC from time zero extrapolated to infinity (AUC ) between groups were all close to 1, with two-sided 90% confidence intervals within 0.8-1.25. Recaticimab showed similar effects on low-density lipoprotein cholesterol levels in all groups, with mean maximum percentage decreases ranging from 56.88% to 59.04%. The percentage changes from baseline in free PCSK9 and other lipid variables were similar across the three groups as well. Treatment-emergent adverse events were reported in 41/53 (77.4%, abdomen), 29/53 (54.7%, upper-arm), and 42/53 (79.2%, thigh) subjects, most of which were mild and resolved without treatment. The incidence of antidrug antibodies among the three groups was comparable. A single subcutaneous injection of 450 mg recaticimab into the abdomen, upper-arm, or thigh was well-tolerated and presented similar PK and PD profiles, which supported the interchangeable use of the three injection sites for patients. ( www. gov ) NCT05370950 2022-05-07.